2017
DOI: 10.1017/s0007114517002549
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a non-restrictive satiating diet on anthropometrics, satiety responsiveness and eating behaviour traits in obese men displaying a high or a low satiety phenotype

Abstract: The aim of this study was to evaluate the impact of a non-restrictive satiating diet in men displaying various degrees of satiety efficiency. In all, sixty-nine obese men aged 41·5 (sd 5·7) years were randomly assigned to a control (10-15, 55-60 and 30 % energy as protein, carbohydrate and lipid, respectively; n 34) or satiating (20-25, 45-50 and 30-35 % energy as protein, carbohydrate and lipid, respectively; n 35) diet for 16 weeks, and were classified as having a low (LSP) or high (HSP) satiety phenotype. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 60 publications
3
39
2
Order By: Relevance
“…Lower weight loss in the LSP is consistent with one previous study in men, which reported that the LSP lost less weight over 16-weeks compared to the HSP (15) . The differences in weight loss between satiety phenotypes were similar across studies (current study: -3.1% versus -6.4%, previous study: -3•3 to -4 3 % versus −5 4 to −6 6 %).…”
Section: Appetite Control During the Programsupporting
confidence: 91%
See 3 more Smart Citations
“…Lower weight loss in the LSP is consistent with one previous study in men, which reported that the LSP lost less weight over 16-weeks compared to the HSP (15) . The differences in weight loss between satiety phenotypes were similar across studies (current study: -3.1% versus -6.4%, previous study: -3•3 to -4 3 % versus −5 4 to −6 6 %).…”
Section: Appetite Control During the Programsupporting
confidence: 91%
“…The current analysis differs to the previous analyses (which reported effects for the overall sample), by focusing specifically on satiety phenotypes. Based on previous research (15) power calculations in G*Power with an of 0.05 and power of 0.80 showed that a sample size of 54 participants would be sufficient to detect significant differences in weight change between satiety phenotypes (23) . Ninety-six women who were overweight or obese and had recently enrolled in a weight loss program were recruited.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, up to now, the characteristics of a healthy diet/body weight reducing program include a low to moderate total, and saturated, lipid intake, and an increase in the relative consumption of protein and of high-fiber, low-GI carbohydrate foods. Recently, we tested the impact of a regimen integrating these features and found that it successfully accentuated body weight loss, while facilitating appetite control in individuals with a low satiety phenotype [ 15 ]. However, this type of study does not permit identifying which constituent of the macronutrient family has the greatest potential to influence energy balance in this context.…”
Section: Introductionmentioning
confidence: 99%